Development of new equipment for intra‐arrest brain cooling that uses cooled oxygen in the lungs: volunteer study. Issue 2 (17th November 2016) - Sakurai, Atsushi; Tagami, Rumi; Ihara, Shingo; Yamaguchi, Junko; Sugita, Atsunori; Sawada, Nami; Komatsu, Tomohide; Hori, Satoshi; Kinoshita, Kosaku
Abstract : Aims: Many experimental studies have reported that intra‐arrest cooling during cardiac arrest is a promising treatment to mitigate brain injury. However, there is no clinically established method for cooling the brain during cardiac arrest. We hypothesized that, as blood flow in the lungs must be very slow during cardiopulmonary resuscitation, the blood could be cooled by ventilating the lungs with cooled oxygen like a radiator, and that this cooled blood would in turn cool the brain. The aim of this study was to develop equipment to cool oxygen for this purpose and to confirm its safety on a group of volunteers. Methods: We developed new equipment that cools oxygen by running it through a vinyl chloride coil submerged in a bottle of water and frozen at −80°C. Using this equipment, seven volunteers were given oxygen by mask, and their blood pressure, heart rate, and peripheral saturation of oxygen were measured. The temperature in the mask was also measured. Results: This equipment was able to decrease the temperature in the mask to −5°C at the Jackson Rees circuit for an oxygen flow of 10 L/min. Among the volunteer group, vital signs were unchanged and the temperature in the mask decreased from 30.1 ± 2.6°C (mean ± standard deviation) to 15.9 ± 9.6°C. No adverse effects were observed in the volunteers after experimentation. Conclusion: We successfully developed new equipment to cool oxygen and established its safety in a volunteer study. Abstract : A new equipment was developed to cool oxygen to cool lung during cardiopulmonary resuscitation for the brain protection. Two sets of the coil/bottle equipment, each administrating oxygen at 10L/min (20L/min totally), were attached to the Jackson Rees circuit and a heat and moisture exchanger with mask.